Change Management in Islamic Colleges - Irwandi, Feri; Junaidah, Junaidah; Fauzan, Ahmad; Fanisyah, Elsah (Universitas Islam Negeri Raden Intan Lampung, 2024)
Changes will always occur in every line of life, so adjustments need to be made for good and progress, especially in the field of education. Change encourages the willingness to adapt and is an opportunity to improve. This research uses a qualitative descriptive approach, with data collection methods in the form of observation, interviews, and documentation which are then processed through the stages of data reduction, data presentation, and conclusion drawing or data verification. The purpose of this study is to analyze change management related to the implementation and evaluation of changes that have been carried out by Sekolah Tinggi Agama Islam Yayasan Pembangunan Kalianda, South Lampung. In findings related to the implementation and evaluation of change, it is known that implementation is carried out in three phases, namely unfreezing, change, and refreezing. Then in the evaluation of change, a thorough analysis is carried out to determine future improvements, ideas, and innovations. In this regard, this research can be a reference in carrying out change management for Islamic educational institutions in the future.